Constructing theory with big result now (BRN): Contribution of Tanzania to the theory of knowledge sharing behaviour - Balozi, Mohamedi Abbasi; Othman, Siti Zubaidah; Mohamed Issa, Mohamed Faisal (International educative research foundation and publisher (IERFP), 2014)
Purpose- This paper intends to discourse development of theory in the Tanzania context, based on potentiality of advancing of knowledge sharing theory globally.The aim of this paper is to develop a theoretical framework which essential for studying knowledge sharing behaviour which is critical significant for the organizational changes and national reforms as well for sustaining in tremendous competition.Moreover, the study established the needs to undergo investigation in order to illustrate the degree of performance of theory in the context of Tanzania, which will depict comparison with developed countries.Methodology- This paper reviewed the theory of planned behaviour and it portrayed TPB as underpinned theory for revising knowledge sharing in the context of Tanzania.Findings- The study revealed propositions which are fundamental in developing theory of planned behaviour for studying knowledge sharing in Tanzania context.Limitations of the study- this paper offers suggestions for proposition testing and direction for further studies in knowledge sharing behaviour.Implication of the study- the paper provides development of theory and practically, the research might provide insight for improving knowledge sharing practices in order to realise organizational development and national reforms(BRN) in the context of Tanzania.Value- This paper relies on theoretical approaches, particularly on advancement of theory of planned of behaviour under addition of the collectivist culture and interpersonal relation towards knowledge sharing behaviour in Tanzania.